Effectiveness of Psycho-Educational Intervention in HIV Patients’ Treatment - Ribeiro, Clarisse; Sarmento e Castro, Rui; Dinis-Ribeiro, Mário; Fernandes, Lia (Frontiers in Psychiatry, 2015)
Adherence to Highly Active Antiretroviral Therapy (HAART) is the main prognostic factor associated with HIV disease progression and death. The aim was to evaluate the effectiveness of a psycho-educational program to promote adherence to HAART in HIV patients. A longitudinal study (n=102) over 9 months in an Infectious Diseases Hospital was carried out. Adherence to HAART was measured with standardized scales and values of viral load. Two groups were defined: adherents and non-adherents. In the latter, a psycho-educational program was implemented and 6 months later measured adherence to HAART. Knowledge about the infection, CD4 T lymphocytes and HIV-ribonucleic acid (HIV-RNA) values were measured before and after this program. The sample was predominantly male (70%), heterosexual (78%), with a mean age of 49 (sd=12.7) years, and 48% of participants were not adhering to HAART. After the program, non-adherence decreased to 21.6%. Knowledge about the infection increased from 79% to 97%. A significant increase in CD4 T lymphocytes (mean 540 to 580) and a decrease in viral load (mean 5411 to 3052) were observed, the latter of statistical significance. This program seems to be feasible and efficient, improving adherence to HAART.